The influence of two teaching approaches on foot loading in skiing beginners - a comparative study - Kurpiers, N.; Gersmann, L.; Reinhart, K.; Eden, N.; Kersting, U. G. (Sensors, 2024)
(1) Background: Alpine skiing, with its long history, has experienced numerous innovations and developments on all levels ranging from technology to fashion over the past 120 years. However, teaching approaches for beginners remained quite consistent for many decades and are mainly grounded in experience. The One-Ski-Method (OSM) is an alternative approach to the predominant snowplow (SP) method with the strategy to initially experience and acquire the elementary positions and actions on one ski in order to subsequently transfer these to two skis. The aim of the study was to compare the effects of the SP and the OSM by assessing the position of the ski via load distribution sensors. (2) Methods: A total of 33 participants were groupwise randomly assigned to the two methods and tested via load insoles on the first and the fifth day on a moderate slope for six turns. Between the two measurements, the groups were instructed according to the SP or the OSM methods, respectively. The data were analyzed via Matlab and SPSS. (3) Results: The OSM group showed a significantly greater forefoot load than the SP group (p = 0.029). The SP group developed a greater rearfoot loading from pre- to post testing. (4) Conclusions: The findings make it perceivable that OSM learners acquire a beneficial specific position on the ski due to the exercises of the OSM.